Features of displays of sense of humor as adaptive mechanism: coping strategy or a defense mechanism? - Олександра Мітрова (Київський національний університет імені Тараса Шевченка, 2015)
This article discusses the sense of humor as a mechanism of psychological overcoming and its join with the social and psychological adapta- tion as a measure of the success of its application; it systemizes scientific developments in the field of humor and coping strategies and provides an overview of studies that investigates a sense of humor as coping mechanism. It also devides the concepts of coping-mechanisms and psycho- logical defenses of personality, which are two different types of reaction on stressing situations. The article presents the results of empirical research organized and held by the author, which examines features of humor because of the peculiarities of application of coping strategies, defense mechanisms and the level of socio-psychological adaptation of personality.

У статті розглянуто питання особливостей прояву почуття гумору як копінг-стратегії на противагу захисним механізмам та його зв'язок із соціально-психологічною адаптацією. Дається характеристика копінг-стратегій та захисних механізмів як механізмів соціально-психологічної адаптації. У статті представлені дані емпіричного дослідження прояву почуття гумору у зв'язку із соціально-психологічною адаптацією, притаманністю застосування копінгів, захисних механізмів, а також із життєвими стилями особистості.
Особливості прояву почуття гумору як адаптаційного механізму: копінг-стратегія чи захисний механізм?
Keywords: дослідження; почуття гумору; копінг-стратегії; психологічне подолання; sense of humor; coping-strategies; psychological overcoming; psychosocial adaptation; research